Speech Entrainment: Rhythmic Predictions Carried by Neural Oscillations - Zoefel, Benedikt (Curr Biol, 2018)
It has been hypothesized that stimulus-aligned brain rhythms reflect predictions about upcoming input. New research shows that these rhythms bias subsequent speech perception, in line with a mechanism of prediction.